Surface Proteoglycans as Mediators in Bacterial Pathogens Infections - García, Beatriz; Merayo-Lloves, Jesús; Martin, Carla; Alcalde, Ignacio; Quirós, Luis M.; Vazquez, Fernando (Frontiers in Microbiology, 2016)
Infectious diseases remain an important global health problem. The interaction of a wide range of pathogen bacteria with host cells from many different tissues is frequently mediated by proteoglycans. These compounds are ubiquitous complex molecules which are not only involved in adherence and colonization, but can also participate in other steps of pathogenesis. To overcome the problem of microbial resistance to antibiotics new therapeutic agents could be developed based on the characteristics of the interaction of pathogens with proteoglycans.